Impact of treatment on cellular immunophenotype in MS: A cross-sectional study. Issue 3 (May 2020) - Cellerino, Maria; Ivaldi, Federico; Pardini, Matteo; Rotta, Gianluca; Vila, Gemma; Bäcker-Koduah, Priscilla; Berge, Tone; Laroni, Alice; Lapucci, Caterina; Novi, Giovanni; Boffa, Giacomo; Sbragia, Elvira; et al.
Abstract : Objective: To establish cytometry profiles associated with disease stages and immunotherapy in MS. Methods: Demographic/clinical data and peripheral blood samples were collected from 227 patients with MS and 82 sex- and age-matched healthy controls (HCs) enrolled in a cross-sectional study at 4 European MS centers (Spain, Italy, Germany, and Norway). Flow cytometry of isolated peripheral blood mononuclear cells was performed in each center using specifically prepared antibody-cocktail Lyotubes; data analysis was centralized at the Genoa center. Differences in immune cell subsets were assessed between groups of untreated patients with relapsing-remitting or progressive MS (RRMS or PMS) and HCs and between groups of patients with RRMS taking 6 commonly used disease-modifying drugs. Results: In untreated patients with MS, significantly higher frequencies of Th17 cells in the RRMS population compared with HC and lower frequencies of B-memory/B-regulatory cells as well as higher percentages of B-mature cells in patients with PMS compared with HCs emerged. Overall, the greatest deviation in immunophenotype in MS was observed by treatment rather than disease course, with the strongest impact found in fingolimod-treated patients. Fingolimod induced a decrease in total CD4 + T cells and in B-mature and B-memory cells and increases in CD4 + and CD8 + T-regulatory and B-regulatory cells. Conclusions: Our highly standardized, multisite cytomics data provide further understanding of treatment impact on MS immunophenotype and could pave the way toward monitoring immune cells to help clinical management of MS individuals.